Tanggung Jawab Perdata dalam Transaksi Crypto Asset: Kajian Terhadap Risiko Kerugian Investor - Fitri Natasha Dachi; Urbanisasi Urbanisasi (Lembaga Pengembangan Kinerja Dosen, 2024)
Crypto asset transactions in Indonesia have rapidly developed alongside financial technology advancements, yet they pose legal challenges concerning investor protection. Under Indonesian civil law, civil liability for investor losses may be based on Article 1243 and Article 1365 of the Civil Code, depending on whether the loss arises from a breach of contract or an unlawful act. Additionally, the Consumer Protection Act may serve as a legal basis in cases involving violations of consumer rights. However, the application of such liability encounters juridical obstacles, including the absence of specific regulations defining the legal status of crypto assets as legal objects, regulatory gaps regarding business actors’ obligations, and evidentiary difficulties due to the anonymous nature of digital transactions. In this context, regulatory reform is essential to establish legal certainty and effective investor protection. The regulation should include digital security standards, transparent risk disclosures, and dispute resolution mechanisms. Active roles of Bappebti and the Financial Services Authority (OJK) in oversight, as well as legal literacy for the public, are critical to creating a responsible and secure crypto asset trading ecosystem.